2019
DOI: 10.1152/ajpendo.00109.2019
|View full text |Cite
|
Sign up to set email alerts
|

The exocyst complex regulates insulin-stimulated glucose uptake of skeletal muscle cells

Abstract: Skeletal muscle handles ~80–90% of the insulin-induced glucose uptake. In skeletal muscle, insulin binding to its cell surface receptor triggers redistribution of intracellular glucose transporter GLUT4 protein to the cell surface, enabling facilitated glucose uptake. In adipocytes, the eight-protein exocyst complex is an indispensable constituent in insulin-induced glucose uptake, as it is responsible for the targeted trafficking and plasma membrane-delivery of GLUT4. However, the role of the exocyst in skele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 54 publications
1
23
0
Order By: Relevance
“…As a critical member of the exocyst, Exo70 was reported to promote invasion via enhancing MMPs secretion in tumor cells [25,26,32], and increased glucose uptake by accelerating inter-endosomal GLUT4 traffic to the plasma membrane in adipocytes [33,34]. In the present study, we reported for the first time that Exo70 promotes cisplatin efflux in EOC cells.…”
Section: Discussionsupporting
confidence: 52%
“…As a critical member of the exocyst, Exo70 was reported to promote invasion via enhancing MMPs secretion in tumor cells [25,26,32], and increased glucose uptake by accelerating inter-endosomal GLUT4 traffic to the plasma membrane in adipocytes [33,34]. In the present study, we reported for the first time that Exo70 promotes cisplatin efflux in EOC cells.…”
Section: Discussionsupporting
confidence: 52%
“…Previously, we demonstrated that the exocyst subunit EXOC5 is essential for insulin-stimulated GLUT4 exocytosis and glucose uptake in cultured rat skeletal myoblasts ( 17 ). To study the consequences of in vivo disruption of Exoc5 and the exocyst, we generated skeletal-muscle-specific Exoc5 conditional knockout ( Exoc5 -SMKO) mice.…”
Section: Resultsmentioning
confidence: 99%
“…There have been very few studies directly examining the role of the exocyst complex in skeletal muscle tissues. We have previously demonstrated that chemical inhibition of the exocyst complex and the heterozygous knockout of Exoc5 lead to a reduction in insulin-stimulated GLUT4 membrane delivery and glucose uptake in rat skeletal myoblasts ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin stimulation promotes re-localization of endogenous complexin-2 to the PM L6 myoblasts and myotubes modified to stably express a chimeric GLUT4 protein tagged with a myc-epitope at its first exofacial loop (L6-GLUT4myc) have been widely used to study insulin-dependent signals and GLUT4 translocation in a muscle background [33,34,39]. Indeed, L6-GLUT4myc myoblasts and L6 myoblasts stably transfected with untagged or HA-tagged GLUT4 represent useful cellular paradigms that retains the main features of GLUT4 traffic, such as significant GLUT4 segregation away from recycling proteins and responsiveness to insulin [32,[40][41][42][43][44][45]. In unstimulated L6-GLUT4myc myoblasts and myotubes (basal condition), endogenous complexin-2 displayed mixed diffuse and punctate distribution throughout the cytosol (Figure 1E).…”
Section: L6 Myoblasts Express Complexin-2mentioning
confidence: 99%